Stability of Pt10Sn3 Clusters Supported on γ‐Al2O3 in Oxidizing Environment: a DFT Comparison of Alloying and Size Effects. Issue 23 (17th November 2022) - Shahrokhi, Masoud; Chizallet, Celine; Loffreda, David; Raybaud, Pascal
Abstract: The understanding of the structure and properties of γ‐Al2 O3 supported platinum‐tin catalysts in oxidizing conditions is of prominent importance for many catalytic reactions. By using density functional theory calculations and ab initio molecular dynamics simulations, we identify the adsorption sites of oxygen atoms on a Pt10 Sn3 /γ‐Al2 O3 (100) cluster model and analyze its reconstruction and electronic charge redistribution. A strengthening of O adsorption is found for the cluster with respect to the Pt3 Sn(111) surface, due to the key role of Al−Pt interfacial sites at low coverage, the ductility and the metastability of the cluster. Moreover, the ab initio ( p O 2 p_O_2, T) thermodynamic phase diagrams show only minor differences between the supported Pt10 Sn3 and Pt13 clusters. Both clusters are much more oxidized than their homologous Pt and Pt3 Sn(111) surfaces, and their oxygen contents may exceed 1 ML. This suggests a stronger size effect than an alloying effect for the oxidation of the metallic PtSn nanoparticles at small size. Abstract : γ‐Al2 O3 Supported Platinum‐Tin Catalysts : Structural and electronic properties of a Pt10 Sn3 /γ‐Al2 O3 (100) cluster model in oxidizing conditions are modelled by DFT and ab initio molecular dynamics. O2 dissociation leads to strongly reconstructed clusters, exhibiting higher oxophilicity that Pt3 Sn(111), assigned to Al−Pt interfacial sites at low coverage, and to the ductility and metastability of the cluster.